85th Meeting of the EBC Analysis Committee, held in Maastricht/NL on 25 May 1997 (BrewingScience, 1997)
Analytica-EBCBreing Analytes Profiency SchemeBarley and Cereal Adjuncts Sub-committeeMalt and Coloured Malt-Sub-committeeHopsWortBeerPackaging and Packaging MaterialsProcess AidsStatisticsInternational MethodsMicrobiology